2011
DOI: 10.1143/apex.4.125701
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Interfacial Reaction Study of Half Cycle Atomic Layer Deposited Al$_{2}$O$_{3}$ on Chemically Treated InP Surfaces

Abstract: The interfacial reactions between atomic layer deposited Al 2 O 3 films on various chemically treated InP(100) surfaces have been investigated by in situ X-ray photoelectron spectroscopy at each half cycle in the deposition process. With the first cycle of trimethyl aluminum, a significant decrease in the amount of indium oxides present on the surface is seen, consistent with the ''clean up'' effect reported for other III-V semiconductor surfaces. However, a concurrent increase in the amount of phosphorous oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 26 publications
2
47
1
Order By: Relevance
“…A unique advantage of ALD method is the ability to uniformly deposit on geometrically complex surfaces [9][10][11]. For this reason, atomic layer deposition method may be used for deposition of the optical thin film on the silicon solar cells as antireflection coating.…”
Section: Introductionmentioning
confidence: 99%
“…A unique advantage of ALD method is the ability to uniformly deposit on geometrically complex surfaces [9][10][11]. For this reason, atomic layer deposition method may be used for deposition of the optical thin film on the silicon solar cells as antireflection coating.…”
Section: Introductionmentioning
confidence: 99%
“…7 One of the advantages of high-k dielectrics grown by atomic layer deposition (ALD) on III-V substrates is the "self cleaning" effect, 7 in which the native oxides are converted by the first pulse of metal precursor during ALD. 8,9 Suri et al have shown, using tetrakis(dimethylamido)hafnium (TDMA-Hf) and H 2 O precursors, that the "self cleaning" effect on GaAs is temperature dependent, with the removal of oxides being more pronounced at 300 C than at the 250 C or 200 C. 10 However, quite different trends for the "self cleaning" effect have been reported on GaAs in comparison to those for acid etched and S-passivated InP. 9,11,12 A less efficient "self cleaning" effect has been observed during thin film deposition (2 nm) of ALD HfO 2 , while the "self cleaning" effect has been reported to be enhanced significantly following thick (8 nm) ALD using tetrakis(ethylmethylamino)hafnium (TEMA-Hf) and water as precursors at a substrate temperature of 300 C. 7 Recently, An et al 13 reported the impact of ALD temperature on HfO 2 deposition on S-passivated InP substrates using TEMA-Hf and water, with a significant "self cleaning" effect occurring at 200 C and 250 C but substantial InP substrate oxidation occurring at 300 C. 13 This apparent variation during ALD HfO 2 on different III-V substrate materials therefore warrants further study.…”
mentioning
confidence: 99%
“…14 Actually, recent in situ "half cycle" studies of ALD HfO 2 and Al 2 O 3 on native oxide and chemically treated InP (100) have shown that no "self cleaning" effect takes place on P-oxides during the initial ALD process. 9,15 In this study, the in situ evolution of a high-k/native oxide and wet chemically treated InP (100) interface during ALD at temperatures of 200 C, 250 C, and 300 C is reported, and the role of ALD temperature in the removal of InP (100) interfacial oxides during the initial stages using TDMA-Hf and water is investigated.…”
mentioning
confidence: 99%
“…6 It was observed for Al 2 O 3 ALD on InP that most of the In-oxide concentration decrease (due to self-cleaning) and complete P-oxide chemical state transformation into more P-rich oxide state took place during the first pulse of TMA. 7 The electrical characteristics of ALD TiO 2 /Al 2 O 3 /(NH 4 ) 2 S-treated InP showed the removal of native oxides by the (NH 4 ) 2 S treatment and ALD-Al 2 O 3 self-cleaning. 8 On the basis of the reported self-cleaning data, it was suggested that the native oxide in the 2 nm thick HfO 2 /InP would be removed entirely during the ALD process.…”
Section: Introductionmentioning
confidence: 95%